Intraoperative fetal heart monitoring for non-obstetric surgery: A systematic review. (July 2019) - Po', Gaia; Olivieri, Carlotta; Rose, Carl H.; Saccone, Gabriele; McCurdy, Rebekah; Berghella, Vincenzo
Abstract: Limited data are available on fetal monitoring during non-obstetric surgery in pregnancy. We performed a systematic review to evaluate the incidence of emergent cesarean delivery performed for non-reassuring fetal heart rate patterns during non-obstetric surgery. Electronic databases were searched from their inception until October 2018 without limit for language. We included studies evaluating at least five cases of intraoperative fetal heart rate monitoring -either with ultrasound or cardiotocography- during non-obstetric surgery in pregnant women at ≥22 weeks of gestation. The primary outcome was the incidence of intraoperative cesarean delivery performed for non-reassuring fetal heart rate monitoring. Non-reassuring fetal heart rate monitoring was defined by attendant personnel, meeting NICHD criteria for category II or III patterns. Data extracted regarded type of study, demographic characteristics, maternal and perinatal outcomes. Statistical analysis was performed for continuous outcomes by calculating mean and standard deviations for appropriate variables. Of 120 studies identified, 4 with 41 cases of intraoperative monitoring met criteria for inclusion and were analyzed. Most (66%) surgeries were indicated for neurological or abdominal maternal issues and were performed under general anesthesia (88%) at a mean gestational age of 28 weeks. Minimal or absent fetal heart variability was noted in most cases and a 10–25 beats per minutes decrease in fetal heart rate baseline was observed in cases with general anesthesia. No intraoperative cesarean deliveries were needed. The incidence of non-reassuring fetal heart rate monitoring was 4.9% (2/41) and were limited to fetal tachycardia during maternal fever. Two (4.9%) cases of non-reassuring fetal heart rate monitoring were noted within the immediate 48 h after surgery, necessitating cesarean delivery. A single case of intrauterine fetal demise occurred four days postoperatively in a woman who had neurosurgery and remained comatose. In conclusion, limited data exist regarding the clinical application of fetal heart rate monitoring at viable gestational ages during non-obstetric surgical procedures. Fetal heart rate monitoring during non-obstetric surgery at ≥22 weeks was not associated with need for intraoperative cesarean delivery, but two (4.9%) cesarean deliveries were performed for non-reassuring fetal heart rate monitoring within 48 h after surgery.